2000
DOI: 10.1023/a:1005560328334
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: All but a small fraction of the hundreds of proteins in a mitochondrion are synthesized in the cytoplasm and imported into the organelle. Water-filled channels are integral to the process of translocating proteins since channels can provide an aqueous pathway through the hydrophobic environment of the membrane. The MCC (multiple conductance channel) and PSC (peptide-sensitive channel) are two high-conductance channels previously identified in electrophysiological studies of mitochondrial membranes. MCC and PSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Comparisons of these activities with those of recombinant proteins Tim23 and Tom40 solidified the assignment of identities (Chich et al, 1991; Fevre et al, 1993, 1994; Henry et al, 1996; Juin et al, 1997; Kinnally et al, 2000; Kunkele et al, 1998b; Thieffry et al, 1992). TOM and TIM23 activities have a peak conductance of ~1 nS in yeast and ~750 pS in mammals (150 mM KCl).…”
Section: The Protein Import Channels Tom Tim23 and Tim22mentioning
confidence: 66%
“…Comparisons of these activities with those of recombinant proteins Tim23 and Tom40 solidified the assignment of identities (Chich et al, 1991; Fevre et al, 1993, 1994; Henry et al, 1996; Juin et al, 1997; Kinnally et al, 2000; Kunkele et al, 1998b; Thieffry et al, 1992). TOM and TIM23 activities have a peak conductance of ~1 nS in yeast and ~750 pS in mammals (150 mM KCl).…”
Section: The Protein Import Channels Tom Tim23 and Tim22mentioning
confidence: 66%
“…In addition to the regulation of transport of ions and small molecules over the mitochondrial membranes, the TSPO also appears to regulate the import of proteins into the mitochondria, including the matrix [ 82 ]. For example, apart from its function as a channel for ions, MCC can serve as the pore of the import complex present in the inner mitochondrial membrane [ 95 ]. In short, MCC is also considered to be a protein import channel.…”
Section: Functional Effects Of Ppix and Synthetic Tspo Ligands In mentioning
confidence: 99%
“…The gating of this protein-selective pore has been extensively studied in patch clamp experiments on isolated mitochondrial membranes. Patch clamping was also instrumental to functional dissection the main TIM23 components (Lohret et al, 1997; Kinnally et al, 2000; Martinez-Caballero et al, 2007a). There are five membrane-spanning TIM23 subunits: Tim23p and Tim17p are thought to be the pore components (Martinez-Caballero et al, 2007a); Tim50p is the main presequence receptor and a putative structural scaffold that links TIM23 to the outer membrane import complex (TOM) (Mokranjac et al, 2009); Tim21p is a transient subunit that has been shown to interact with TOM or with respiratory complexes (Chacinska et al, 2005); Mgr2p/Romo1 bridges TIM23 to the presequence translocase-associated motor (PAM) and is thought to regulate the lateral release of proteins harboring stop-transfer sequences.…”
Section: Introductionmentioning
confidence: 99%